Circulating β cell‐specific CD8+ T cells restricted by high‐risk HLA class I molecules show antigen experience in children with and at risk of type 1 diabetes. (10th November 2019) - Yeo, L.; Pujol‐Autonell, I.; Baptista, R.; Eichmann, M.; Kronenberg‐Versteeg, D.; Heck, S.; Dolton, G.; Sewell, A. K.; Härkönen, T.; Mikk, M.‐L.; Toppari, J.; Veijola, R.; et al.
Summary: In type 1 diabetes (T1D), autoreactive cytotoxic CD8 + T cells are implicated in the destruction of insulin‐producing β cells. The HLA‐B*3906 and HLA‐A*2402 class I genes confer increased risk and promote early disease onset, suggesting that CD8 + T cells that recognize peptides presented by these class I molecules on pancreatic β cells play a pivotal role in the autoimmune response. We examined the frequency and phenotype of circulating preproinsulin (PPI)‐specific and insulin B (InsB)‐specific CD8 + T cells in HLA‐B*3906 + children newly diagnosed with T1D and in high‐risk HLA‐A*2402 + children before the appearance of disease‐specific autoantibodies and before diagnosis of T1D. Antigen‐specific CD8 + T cells were detected using human leucocyte antigen (HLA) class I tetramers and flow cytometry was used to assess memory status. In HLA‐B*3906 + children with T1D, we observed an increase in PPI5–12 ‐specific transitional memory CD8 + T cells compared to non‐diabetic, age‐ and HLA‐matched subjects. Furthermore, PPI5–12 ‐specific CD8 + T cells in HLA‐B*3906 + children with T1D showed a significantly more antigen‐experienced phenotype compared to polyclonal CD8 + T cells. In longitudinal samples from high‐risk HLA‐A*2402 + children, the percentage of terminal effector cells within the InsB15–24 ‐specific CD8 + T cells was increased before diagnosis relative to samples taken before the appearance of autoantibodies. This is the first study, to our knowledge, to report HLA‐B*3906 ‐restricted autoreactive CD8 + T cells in T1D. Collectively, our results provide evidence that β cell‐reactive CD8 + T cells restricted by disease‐associated HLA class I molecules display an antigen‐experienced phenotype and acquire enhanced effector function during the period leading to clinical diagnosis, implicating these cells in driving disease. Abstract : In this study, we characterised circulating autoreactive CD8 + T cells in children with type 1 diabetes with HLA‐B*3906 + and HLA‐A*2402 + genotypes which are associated with increased risk and early onset of disease. In HLA‐B*3906 + children with newly diagnosed type 1 diabetes, we observed an increase in PPI5–12 ‐specific transitional memory CD8 + T cells compared to non‐diabetic, age‐ and HLA‐matched subjects. Furthermore, PPI5–12 ‐specific CD8 + T cells in HLA‐B*3906 + children with T1D showed a significantly more antigen‐experienced phenotype compared to polyclonal CD8 + T cells. Further, in longitudinal samples from high‐risk HLA‐A*2402 + children, the percentage of terminal effector cells within the InsB15–24 ‐specific CD8 + T cell population was increased before diagnosis relative to samples taken before the appearance of autoantibodies.